A new dynamic two-stage mathematical programming model under uncertainty for project evaluation and selection - Tavana, Madjid; Khosrojerdi, Ghasem; Mina, Hassan; Rahman, Amirah (Computers & Industrial Engineering)

An Exact Branch-and-Price Algorithm for Scheduling Rescue Units during Disaster Response - Rauchecker, Gerhard; Schryen, Guido (European Journal of Operational Research)
In disaster operations management, a challenging task for rescue organizations occurs when they have to assign and schedule their rescue units to emerging incidents under time pressure in order to reduce the overall resulting harm. Of particular importance in practical scenarios is the need to consider collaboration of rescue units. This task has hardly been addressed in the literature. We contribute to both modeling and solving this problem by (1) conceptualizing the situation as a type of scheduling problem, (2) modeling it as a binary linear minimization problem, (3) suggesting a branch-and-price algorithm, which can serve as both an exact and heuristic solution procedure, and (4) conducting computational experiments - including a sensitivity analysis of the effects of exogenous model parameters on execution times and objective value improvements over a heuristic suggested in the literature - for different practical disaster scenarios. The results of our computational experiments show that most problem instances of practically feasible size can be solved to optimality within ten minutes. Furthermore, even when our algorithm is terminated once the first feasible solution has been found, this solution is in almost all cases competitive to the optimal solution and substantially better than the solution obtained by the best known algorithm from the literature. This performance of our branch-and-price algorithm enables rescue organizations to apply our procedure in practice, even when the time for decision making is limited to a few minutes. By addressing a very general type of scheduling problem, our approach applies to various scheduling situations.
Keywords: OR in disaster relief; disaster operations management; scheduling; branch-and-price

Using High Performance Computing for Unrelated Parallel Machine Scheduling with Sequence-Dependent Setup Times: Development and Computational Evaluation of a Parallel Branch-and-Price Algorithm - Rauchecker, Gerhard; Schryen, Guido (Computers & Operations Research)
Scheduling problems are essential for decision making in many academic disciplines, including operations management, computer science, and information systems. Since many scheduling problems are NP-hard in the strong sense, there is only limited research on exact algorithms and how their efficiency scales when implemented on parallel computing architectures. We address this gap by (1) adapting an exact branch-and-price algorithm to a parallel machine scheduling problem on unrelated machines with sequence- and machine-dependent setup times, (2) parallelizing the adapted algorithm by implementing a distributed-memory parallelization with a master/worker approach, and (3) conducting extensive computational experiments using up to 960 MPI processes on a modern high performance computing cluster. With our experiments, we show that the efficiency of our parallelization approach can lead to superlinear speedup but can vary substantially between instances. We further show that the wall time of serial execution can be substantially reduced through our parallelization, in some cases from 94 hours to less than six minutes when our algorithm is executed on 960 processes.
Keywords: parallel machine scheduling with setup times; parallel branch-and-price algorithm; high performance computing; master/worker parallelization

Walking the Middle Path: How Medium Trade-off Exposure Leads to Higher Consumer Satisfaction in Recommender Agents - Schuhbeck, Veronika; Siegfried, Nils; Dorner, Verena; Benlian, Alexander; Scholz, Michael; Schryen, Guido (Proceedings of the 14. Internationale Tagung Wirtschaftsinformatik)
Recommender Agents (RAs) facilitate consumers’ online purchase decisions for complex, multi-attribute products. As not all combinations of attribute levels can be obtained, users are forced into trade-offs. The exposure of trade-offs in a RA has been found to affect consumers’ perceptions. However, little is known about how different preference elicitation methods in RAs affect consumers by varying degrees of trade-off exposure. We propose a research model that investigates how different levels of trade-off exposure cognitively and affectively influence consumers’ satisfaction with RAs. We operationalize these levels in three different RA types and test our hypotheses in a laboratory experiment with 116 participants. Our results indicate that with increasing tradeoff exposure, perceived enjoyment and perceived control follow an inverted Ushaped relationship. Hence, RAs using preference elicitation methods with medium trade-off exposure yield highest consumer satisfaction. This contributes to the understanding of trade-offs in RAs and provides valuable implications to e-commerce practitioners.
Keywords: Recommender Agents; Preference Elicitation Method; Trade-off Exposure; Customer Satisfaction

Exploiting Counterfactuals for Scalable Stochastic Optimization - Kuhlemann, Stefan; Sellmann, Meinolf; Tierney, Kevin (Lecture Notes in Computer Science)

High-Performance Business Computing – Parallel Algorithms and Implementations for Solving Problems in Operations Research and Data Analysis - Schryen, Guido; Kliewer, Natalia; Borndörfer, Ralf; Koch, Thorsten (OR News)

An integrated data envelopment analysis and mixed integer non-linear programming model for linearizing the common set of weights - Toloo, Mehdi; Tavana, Madjid; Santos-Arteaga, Francisco J. (Central European Journal of Operations Research)

A tuned hybrid intelligent fruit fly optimization algorithm for fuzzy rule generation and classification - Mousavi, Seyed Mohsen; Tavana, Madjid; Alikar, Najmeh; Zandieh, Mostafa (Neural Computing and Applications)

A New Method for Solving Dual DEA Problems with Fuzzy Stochastic Data - Ebrahimnejad, Ali; Tavana, Madjid; Nasseri, Seyed Hadi; Gholami, Omid (International Journal of Information Technology & Decision Making)

A fuzzy multi-objective multi-period network DEA model for efficiency measurement in oil refineries - Tavana, Madjid; Khalili-Damghani, Kaveh; Santos Arteaga, Francisco J.; Hosseini, Amineh (Computers & Industrial Engineering)

The role of anticipated emotions and the value of information in determining sequential search incentives - Di Caprio, Debora; Santos-Arteaga, Francisco J.; Tavana, Madjid (Operations Research Perspectives)

Tradable mobility permit with Bitcoin and Ethereum – A Blockchain application in transportation - Asadi Bagloee, Saeed; Tavana, Madjid; Withers, Glenn; Patriksson, Michael; Asadi, Mohsen (Internet of Things)

A new bi-level data envelopment analysis model for efficiency measurement and target setting - Razavi Hajiagha, Seyed Hossein; Amoozad Mahdiraji, Hannan; Tavana, Madjid (Measurement)

A Malmquist Productivity Index with Directional Distance Function and Uncertain Data - Aghayi, NAZILA; Tavana, Madjid; Maleki, Bentolhoda (Scientia Iranica)

The impact of interwoven integration practices on supply chain value addition and firm performance - -, Shashi; Tavana, Madjid; Shabani, Amir; Singh, Rajwinder (Journal of Industrial Engineering International)

An improved particle swarm optimization model for solving homogeneous discounted series-parallel redundancy allocation problems - Mousavi, Seyed Mohsen; Alikar, Najmeh; Tavana, Madjid; Di Caprio, Debora (Journal of Intelligent Manufacturing)

A hybrid data envelopment analysis and game theory model for performance measurement in healthcare - Zare, Habib; Tavana, Madjid; Mardani, Abbas; Masoudian, Sepideh; Kamali Saraji, Mahyar (Health Care Management Science)

A dynamic multi-stage slacks-based measure data envelopment analysis model with knowledge accumulation and technological evolution - Santos Arteaga, Francisco J.; Tavana, Madjid; Di Caprio, Debora; Toloo, Mehdi (European Journal of Operational Research)

Dynamic effects of learning on the innovative outputs and productivity in Spanish multinational enterprises - Santos-Arteaga, Francisco J.; Torrecillas, Celia; Tavana, Madjid (The Journal of Technology Transfer)

A predictive analytics framework for identifying patients at risk of developing multiple medical complications caused by chronic diseases - Talaei-Khoei, Amir; Tavana, Madjid; Wilson, James M. (Artificial Intelligence in Medicine)

A chance-constrained portfolio selection model with random-rough variables - Tavana, Madjid; Khanjani Shiraz, Rashed; Di Caprio, Debora (Neural Computing and Applications)

A novel hybrid method for selecting soccer players during the transfer season - Nasiri, Mohammad Mahdi; Ranjbar, Mojtaba; Tavana, Madjid; Santos Arteaga, Francisco J.; Yazdanparast, Reza (Expert Systems)

A novel three-stage distance-based consensus ranking method - Aghayi, Nazila; Tavana, Madjid (Journal of Industrial Engineering International)

An optimization model for traceable closed-loop supply chain networks - Hajipour, Vahid; Tavana, Madjid; Di Caprio, Debora; Akhgar, Majid; Jabbari, Yasaman (Applied Mathematical Modelling)

A hybrid mathematical programming model for optimal project portfolio selection using fuzzy inference system and analytic hierarchy process - Tavana, Madjid; Khosrojerdi, Ghasem; Mina, Hassan; Rahman, Amirah (Evaluation and Program Planning)

Decision Support for the Optimal Coordination of Spontaneous Volunteers in Disaster Relief - Rauchecker, Gerhard; Schryen, Guido (Proceedings of the 15th International Conference on Information Systems for Crisis Response and Management)
When responding to natural disasters, professional relief units are often supported by many volunteers which are not affiliated to humanitarian organizations. The effective coordination of these volunteers is crucial to leverage their capabilities and to avoid conflicts with professional relief units. In this paper, we empirically identify key requirements that professional relief units pose on this coordination. Based on these requirements, we suggest a decision model. We computationally solve a real-world instance of the model and empirically validate the computed solution in interviews with practitioners. Our results show that the suggested model allows for solving volunteer coordination tasks of realistic size near-optimally within short time, with the determined solution being well accepted by practitioners. We also describe in this article how the suggested decision support model is integrated in the volunteer coordination system which we develop in joint cooperation with a disaster management authority and a software development company.
Keywords: Coordination of spontaneous volunteers; volunteer coordination system; decision support; scheduling optimization model; linear programming

Classifying the Ideational Impact of IS Review Articles: A Natural Language Processing Based Approach - Prester, Julian; Wagner, Gerit; Schryen, Guido (Proceedings of the 2018 International Conference on Information Systems (ICIS 2018))

Security in Highly Connected IT Systems – Results of the Bavarian Research Alliance FORSEC - Schillinger, Rolf; Schryen, Guido

Information Security Investments: An Exploratory Multiple Case Study on Decision-Making, Evaluation and Learning - Weishäupl, Eva; Yasasin, Emrah; Schryen, Guido (Computers & Security)
The need to protect resources against attackers is reflected by huge information security investments of firms worldwide. In the presence of budget constraints and a diverse set of assets to protect, organizations have to decide in which IT security measures to invest, how to evaluate those investment decisions, and how to learn from past decisions to optimize future security investment actions. While the academic literature has provided valuable insights into these issues, there is a lack of empirical contributions. To address this lack, we conduct a theory-based exploratory multiple case study. Our case study reveals that (1) firms? investments in information security are largely driven by external environmental and industry-related factors, (2) firms do not implement standardized decision processes, (3) the security process is perceived to impact the business process in a disturbing way, (4) both the implementation of evaluation processes and the application of metrics are hardly existent and (5) learning activities mainly occur at an ad-hoc basis.
Keywords: Information Security Investments; Multiple Case Study; Organizations; Single Loop Learning; Double Loop Learning

Information Systems Design Science Research and Cumulative Knowledge Development: An Exploratory Study - Schuster, Richard; Wagner, Gerit; Schryen, Guido (Proceedings of the 2018 International Conference on Information Systems (ICIS 2018))

Heuristics and Simulation for Water Tank Optimization - Hallmann, Corinna; Burmeister, Sascha Christian; Wissing, Michaela; Suhl, Leena (Communications in Computer and Information Science)

Model Generator for Water Distribution Systems - Hallmann, Corinna; Kuhlemann, Stefan (Operations Research Proceedings)

Efficiency measurement in data envelopment analysis in the presence of ordinal and interval data - Ebrahimi, Bohlool; Tavana, Madjid; Rahmani, Morteza; Santos-Arteaga, Francisco J. (Neural Computing and Applications)

A bank merger predictive model using the Smoluchowski stochastic coagulation equation and reverse engineering - Banakar, Zahra; Tavana, Madjid; Huff, Brian; Di Caprio, Debora (International Journal of Bank Marketing)

A novel common set of weights method for multi-period efficiency measurement using mean-variance criteria - Razavi Hajiagha, Seyed Hossein; Amoozad Mahdiraji, Hannan; Tavana, Madjid; Hashemi, Shide Sadat (Measurement)

A hybrid desirability function approach for tuning parameters in evolutionary optimization algorithms - Mobin, Mohammadsadegh; Mousavi, Seyed Mohsen; Komaki, Mohammad; Tavana, Madjid (Measurement)

Chance-constrained data envelopment analysis modeling with random-rough data - Shiraz, Rashed Khanjani; Tavana, Madjid; Di Caprio, Debora (RAIRO - Operations Research)

Impact of incentive schemes and personality-tradeoffs on two-agent coopetition with numerical estimations - Chión, Sergio J.; Charles, V.; Tavana, Madjid (Measurement)

An intuitionistic fuzzy-grey superiority and inferiority ranking method for third-party reverse logistics provider selection - Tavana, Madjid; Zareinejad, Mohsen; Santos-Arteaga, Francisco J. (International Journal of Systems Science: Operations & Logistics)

Multi-stage supply chain network solution methods: hybrid metaheuristics and performance measurement - Tavana, Madjid; Santos-Arteaga, Francisco J.; Mahmoodirad, Ali; Niroomand, Sadegh; Sanei, Masoud (International Journal of Systems Science: Operations & Logistics)

An evolutionary computation approach to solving repairable multi-state multi-objective redundancy allocation problems - Tavana, Madjid; Khalili-Damghani, Kaveh; Di Caprio, Debora; Oveisi, Zeynab (Neural Computing and Applications)

STRATEGIC SIGNALING AND NEW TECHNOLOGICALLY SUPERIOR PRODUCT INTRODUCTION: A GAME-THEORETIC MODEL WITH SIMULATION - Tavana, Madjid; Caprio, Debora Di; Santos-Arteaga, Francisco J. (Technological and Economic Development of Economy)

A novel two-stage DEA production model with freely distributed initial inputs and shared intermediate outputs - Izadikhah, Mohammad; Tavana, Madjid; Di Caprio, Debora; Santos-Arteaga, Francisco J. (Expert Systems with Applications)

A novel genetic algorithm based method for solving continuous nonlinear optimization problems through subdividing and labeling - Esmaelian, Majid; Tavana, Madjid; Santos-Arteaga, Francisco J.; Vali, Masoumeh (Measurement)

A new dynamic range directional measure for two-stage data envelopment analysis models with negative data - Tavana, Madjid; Izadikhah, Mohammad; Di Caprio, Debora; Farzipoor Saen, Reza (Computers & Industrial Engineering)

An aggregation method for solving group multi-criteria decision-making problems with single-valued neutrosophic sets - Sodenkamp, Mariya A.; Tavana, Madjid; Di Caprio, Debora (Applied Soft Computing)

An Artificial Neural Network and Bayesian Network model for liquidity risk assessment in banking - Tavana, Madjid; Abtahi, Amir-Reza; Di Caprio, Debora; Poortarigh, Maryam (Neurocomputing)

An integrated location-inventory-routing humanitarian supply chain network with pre- and post-disaster management considerations - Tavana, Madjid; Abtahi, Amir-Reza; Di Caprio, Debora; Hashemi, Reza; Yousefi-Zenouz, Reza (Socio-Economic Planning Sciences)

A hybrid DEA-MOLP model for public school assessment and closure decision in the City of Philadelphia - Tavana, Madjid; Ebrahimnejad, Ali; Santos-Arteaga, Francisco J.; Mansourzadeh, Seyed Mehdi; Matin, Reza Kazemi (Socio-Economic Planning Sciences)

Efficiency decomposition and measurement in two-stage fuzzy DEA models using a bargaining game approach - Tavana, Madjid; Khalili-Damghani, Kaveh; Santos Arteaga, Francisco J.; Mahmoudi, Reza; Hafezalkotob, Ashkan (Computers & Industrial Engineering)

A discrete cuckoo optimization algorithm for consolidation in cloud computing - Tavana, Madjid; Shahdi-Pashaki, Saleh; Teymourian, Ehsan; Santos-Arteaga, Francisco J.; Komaki, Mohammad (Computers & Industrial Engineering)

The value of information as a verification and regret-preventing mechanism in algorithmic search environments - Tavana, Madjid; Santos-Arteaga, Francisco J.; Di Caprio, Debora (Information Sciences)

An extended stochastic VIKOR model with decision maker's attitude towards risk - Tavana, Madjid; Di Caprio, Debora; Santos-Arteaga, Francisco J. (Information Sciences)

Algorithms for Max-Min Share Fair Allocation of Indivisible Chores - Aziz, Haris; Rauchecker, Gerhard; Schryen, Guido; Walsh, Toby (Thirty-First AAAI Conference on Artificial Intelligence (AAAI-17))
We consider Max-min Share (MmS) fair allocations of indivisible chores (items with negative utilities). We show that allocation of chores and classical allocation of goods (items with positive utilities) have some fundamental connections but also differences which prevent a straightforward application of algorithms for goods in the chores setting and viceversa. We prove that an MmS allocation does not need to exist for chores and computing an MmS allocation - if it exists - is strongly NP-hard. In view of these non-existence and complexity results, we present a polynomial-time 2-approximation algorithm for MmS fairness for chores. We then introduce a new fairness concept called optimal MmS that represents the best possible allocation in terms of MmS that is guaranteed to exist. We use connections to parallel machine scheduling to give (1) a polynomial-time approximation scheme for computing an optimal MmS allocation when the number of agents is fixed and (2) an effective and efficient heuristic with an ex-post worst-case analysis.

Exploring the Scientific Impact of Information Systems Design Science Research: A Scientometric Study - Wagner, Gerit; Prester, Julian; Schryen, Guido (38th International Conference on Information Systems)
Design science is a fundamental research stream that contends its position in the information systems discipline. While ongoing debates address the relative importance of design science contributions in the information systems community, insights into the scientific impact of design science research (DSR) are missing and this lack of understanding arguably poses challenges to an informed discourse. To identify the most influential papers and those factors that explain their scientific impact, this paper presents an exploratory study of the scientific impact of DSR papers published in the AIS Senior Scholars' Basket of Journals. We uncover the current DSR landscape by taking stock of influential papers and theories and develop a model to explain the scientific impact of DSR papers. Our findings show that scientific impact is significantly explained by theorization and novelty. We discuss how the implications of our work can be projected on the overarching discourse on DSR.

High-Performance Business Computing - Effizienzsteigerung durch Parallelisierung - Schryen, Guido; Hristova, Diana (Smart Data Radar (Deutsche Bank))

Literature Reviews in IS Research: What Can Be Learnt from the Past and Other Fields? - Schryen, Guido; Benlian, Alexander; Rowe, Frantz; Shirley, Gregor; Larsen, Kai; Petter, Stacie; Paré, Guy; Wagner, Gerit; Haag, Steffi; Yasasin, Emrah (Communications of the AIS)
Literature reviews (LRs) are recognized for their increasing impact in the information systems literature. Methodologists have drawn attention to the question of how we can leverage the value of LRs to preserve and generate knowledge. The panelists who participated in the discussion of ?Standalone Literature Reviews in IS Research: What Can Be Learnt from the Past and Other Fields?? at ICIS 2016 in Dublin acknowledged this significant issue and debated a) what the IS field can learn from other fields and where IS-specific challenges occur, b) how the IS field should move forward to foster the genre of LRs, and c) what best practices are to train doctoral IS students in publishing LRs. This article reports the key takeaways of this panel discussion. Guidance for IS scholars is provided on how to conduct LRs that contribute to the cumulative knowledge development within and across the IS field to best prepare the next generation of IS scholars.
Keywords: Literature Review; Review Methodology; Research Methodology; Doctoral Training

A configuration-based recommender system for supporting e-commerce decisions - Scholz, Michael; Dorner, Verena; Schryen, Guido; Benlian, Alexander (European Journal of Operational Research)
Multi-attribute value theory (MAVT)-based recommender systems have been proposed for dealing with issues of existing recommender systems, such as the cold-start problem and changing preferences. However, as we argue in this paper, existing MAVT-based methods for measuring attribute importance weights do not fit the shopping tasks for which recommender systems are typically used. These methods assume well-trained decision makers who are willing to invest time and cognitive effort, and who are familiar with the attributes describing the available alternatives and the ranges of these attribute levels. Yet, recommender systems are most often used by consumers who are usually not familiar with the available attributes and ranges and who wish to save time and effort. Against this background, we develop a new method, based on a product configuration process, which is tailored to the characteristics of these particular decision makers. We empirically compare our method to SWING, ranking-based conjoint analysis and TRADEOFF in a between-subjects laboratory experiment with 153 participants. Results indicate that our proposed method performs better than TRADEOFF and CONJOINT and at least as well as SWING in terms of recommendation accuracy, better than SWING and TRADEOFF and at least as well as CONJOINT in terms of cognitive load, and that participants were faster with our method than with any other method. We conclude that our method is a promising option to help support consumers' decision processes in e-commerce shopping tasks.
Keywords: E-Commerce; Recommender System; Attribute Weights; Configuration System; Decision Support

Simulating Storage Policies for an Automated Grid-Based Warehouse System - Beckschäfer, Michaela; Malberg, Simon; Tierney, Kevin; Weskamp, Christoph (Lecture Notes in Computer Science)

An application of an integrated ANP–QFD framework for sustainable supplier selection - Tavana, Madjid; Yazdani, Morteza; Di Caprio, Debora (International Journal of Logistics Research and Applications)

Drone shipping versus truck delivery in a cross-docking system with multiple fleets and products - Tavana, Madjid; Khalili-Damghani, Kaveh; Santos-Arteaga, Francisco J.; Zandi, Mohammad-Hossein (Expert Systems with Applications)

The effect of preference similarity on the formation of clusters and the connectivity of social networks - Tavana, Madjid; Santos-Arteaga, Francisco J.; Di Caprio, Debora (Computers in Human Behavior)

A fuzzy multi-criteria spatial decision support system for solar farm location planning - Tavana, Madjid; Santos Arteaga, Francisco J.; Mohammadi, Somayeh; Alimohammadi, Moslem (Energy Strategy Reviews)

A multi-objective multi-state series-parallel redundancy allocation model using tuned meta-heuristic algorithms - Alikar, Najmeh; Mousavi, Seyed Mohsen; Tavana, Madjid; Niaki, S.T.A. (International Journal of Systems Science: Operations & Logistics)

The emergence of inclusive and exclusive virtual communities determined by the preferences of their users - Di Caprio, Debora; Santos-Arteaga, Francisco J.; Tavana, Madjid (Journal of Ambient Intelligence and Humanized Computing)

A hybrid goal programming and dynamic data envelopment analysis framework for sustainable supplier evaluation - Tavana, Madjid; Shabanpour, Hadi; Yousefi, Saeed; Farzipoor Saen, Reza (Neural Computing and Applications)

Fuzzy chance-constrained geometric programming: the possibility, necessity and credibility approaches - Khanjani Shiraz, Rashed; Tavana, Madjid; Fukuyama, Hirofumi; Di Caprio, Debora (Operational Research)

A novel method for selecting a single efficient unit in data envelopment analysis without explicit inputs/outputs - Toloo, Mehdi; Tavana, Madjid (Annals of Operations Research)

Innovation dynamics and labor force restructuring with asymmetrically developed national innovation systems - Santos-Arteaga, Francisco J.; Di Caprio, Debora; Tavana, Madjid; O’Connor, Aidan (International Business Review)

A multiple correspondence analysis model for evaluating technology foresight methods - Esmaelian, Majid; Tavana, Madjid; Di Caprio, Debora; Ansari, Reza (Technological Forecasting and Social Change)

A customized genetic algorithm for solving multi-period cross-dock truck scheduling problems - Khalili-Damghani, Kaveh; Tavana, Madjid; Santos-Arteaga, Francisco J.; Ghanbarzad-Dashti, Mahdokht (Measurement)

A flexible cross-efficiency fuzzy data envelopment analysis model for sustainable sourcing - Hatami-Marbini, Adel; Agrell, Per J.; Tavana, Madjid; Khoshnevis, Pegah (Journal of Cleaner Production)

FORMALISING THE DEMAND FOR TECHNOLOGICAL INNOVATIONS: RATIONAL HERDS, MARKET FRICTIONS AND NETWORK EFFECTS - SANTOS-ARTEAGA, FRANCISCO J.; CAPRIO, DEBORA DI; Tavana, Madjid; O'CONNOR, AIDAN (International Journal of Innovation Management)

A Novel Decision Support Framework for Computing Expected Utilities from Linguistic Evaluations - Di Caprio, Debora; Santos-Arteaga, Francisco J.; Tavana, Madjid (International Journal of Uncertainty, Fuzziness and Knowledge-Based Systems)

A bi-objective multi-period series-parallel inventory-redundancy allocation problem with time value of money and inflation considerations - Alikar, Najmeh; Mousavi, Seyed Mohsen; Ghazilla, Raja Ariffin Raja; Tavana, Madjid; Olugu, Ezutah Udoncy (Computers & Industrial Engineering)

Application of the NSGA-II algorithm to a multi-period inventory-redundancy allocation problem in a series-parallel system - Alikar, Najmeh; Mousavi, Seyed Mohsen; Raja Ghazilla, Raja Ariffin; Tavana, Madjid; Olugu, Ezutah Udoncy (Reliability Engineering & System Safety)

A redundancy detection algorithm for fuzzy stochastic multi-objective linear fractional programming problems - Khanjani Shiraz, Rashed; Charles, Vincent; Tavana, Madjid; Di Caprio, Debora (Stochastic Analysis and Applications)

A multi-user decision support system for online city bus tour planning - Bagloee, Saeed Asadi; Tavana, Madjid; Di Caprio, Debora; Asadi, Mohsen; Heshmati, Mitra (Journal of Modern Transportation)

A logit-based model for measuring the effects of transportation infrastructure on land value - Asadi Bagloee, Saeed; Heshmati, Mitra; Tavana, Madjid; Di Caprio, Debora (Transportation Planning and Technology)

Recent Fuzzy Generalisations of Rough Sets Theory: A Systematic Review and Methodological Critique of the Literature - Mardani, Abbas; Nilashi, Mehrbakhsh; Antucheviciene, Jurgita; Tavana, Madjid; Bausys, Romualdas; Ibrahim, Othman (Complexity)

A multi-criteria perception-based strict-ordering algorithm for identifying the most-preferred choice among equally-evaluated alternatives - Tavana, Madjid; Di Caprio, Debora; Santos-Arteaga, Francisco J. (Information Sciences)

Projekt KUBAS: Koordination ungebundener Vor-Ort-Helfer - Rauchecker, Gerhard; Schryen, Guido (Im Einsatz)

Factors Affecting the Scientific Impact of Literature Reviews: A Scientometric Study - Wagner, Gerit; Prester, Julian; Roche, Maria; Benlian, Alexander; Schryen, Guido (International Conference on Information Systems)

Development of two novel face-recognition CAPTCHAs: a security and usability study - Schryen, Guido; Wagner, Gerit; Schlegel, Alexander (Computers & Security)
CAPTCHAs are challenge-response tests that aim at preventing unwanted machines, including bots, from accessing web services while providing easy access for humans. Recent advances in artificial-intelligence based attacks show that the level of security provided by many state-of-the-art text-based CAPTCHAs is declining. At the same time, techniques for distorting and obscuring the text, which are used to maintain the level of security, make text-based CAPTCHAs diffcult to solve for humans, and thereby further degrade usability. The need for developing alternative types of CAPTCHAs which improve both, the current security and usability levels, has been emphasized by several researchers. With this study, we contribute to research through (1) the development of two new face recognition CAPTCHAs (Farett-Gender and Farett-Gender&Age), (2) the security analysis of both procedures, and (3) the provision of empirical evidence that one of the suggested CAPTCHAs (Farett-Gender) is similar to Google's reCAPTCHA and better than KCAPTCHA concerning effectiveness (error rates), superior to both regarding learnability and satisfaction but not effciency.
Keywords: CAPTCHA; Usability; Facial features; Gender classiffcation; Age classification; Face recognition reverse Turing test

A secured context-aware tourism recommender system using artificial bee colony and simulated annealing - Roy, Arup; Tavana, Madjid; Banerjee, Soumya; Caprio, Debora Di (International Journal of Applied Management Science)

Robust efficiency measurement with common set of weights under varying degrees of conservatism and data uncertainty - Aghayi, Nazila; Tavana, Madjid; Raayatpanah, Mohammad Ali (European J. of Industrial Engineering)

Optimistic and pessimistic performance and congestion analysis in fuzzy data envelopment analysis - Khodabakhshi, Mohamad; Tavana, Madjid; Abootaleb, Fatemeh Baghbani (International Journal of Logistics Systems and Management)

Autonomous vehicles: challenges, opportunities, and future implications for transportation policies - Bagloee, Saeed Asadi; Tavana, Madjid; Asadi, Mohsen; Oliver, Tracey (Journal of Modern Transportation)

A bi-objective inventory optimization model under inflation and discount using tuned Pareto-based algorithms: NSGA-II, NRGA, and MOPSO - Mousavi, Seyed Mohsen; Sadeghi, Javad; Niaki, Seyed Taghi Akhavan; Tavana, Madjid (Applied Soft Computing)

An Improved Method for Edge Detection and Image Segmentation Using Fuzzy Cellular Automata - Shahverdi, Reza; Tavana, Madjid; Ebrahimnejad, Ali; Zahedi, Khadijeh; Omranpour, Hesam (Cybernetics and Systems)

An integrated data envelopment analysis and free disposal hull framework for cost-efficiency measurement using rough sets - Khanjani Shiraz, Rashed; Fukuyama, Hirofumi; Tavana, Madjid; Di Caprio, Debora (Applied Soft Computing)

An optimal sequential information acquisition model subject to a heuristic assimilation constraint - Di Caprio, Debora; Santos-Arteaga, Francisco J.; Tavana, Madjid (Benchmarking: An International Journal)

An integrated data envelopment analysis and simulation method for group consensus ranking - Ebrahimnejad, Ali; Tavana, Madjid; Santos-Arteaga, Francisco J. (Mathematics and Computers in Simulation)

A conceptual analytic network model for evaluating and selecting third-party reverse logistics providers - Tavana, Madjid; Zareinejad, Mohsen; Santos-Arteaga, Francisco J.; Kaviani, Mohamad Amin (The International Journal of Advanced Manufacturing Technology)

Solving Geometric Programming Problems with Normal, Linear and Zigzag Uncertainty Distributions - Khanjani Shiraz, Rashed; Tavana, Madjid; Di Caprio, Debora; Fukuyama, Hirofumi (Journal of Optimization Theory and Applications)

Multi-objective multi-layer congested facility location-allocation problem optimization with Pareto-based meta-heuristics - Hajipour, Vahid; Fattahi, Parviz; Tavana, Madjid; Di Caprio, Debora (Applied Mathematical Modelling)

Modeling synergies in multi-criteria supplier selection and order allocation: An application to commodity trading - Sodenkamp, Mariya A.; Tavana, Madjid; Di Caprio, Debora (European Journal of Operational Research)

An artificial immune algorithm for ergonomic product classification using anthropometric measurements - Tavana, Madjid; Kazemi, Mohammad Reza; Vafadarnikjoo, Amin; Mobin, Mohammadsadegh (Measurement)

A two-stage data envelopment analysis model for measuring performance in three-level supply chains - Tavana, Madjid; Kaviani, Mohamad Amin; Di Caprio, Debora; Rahpeyma, Bentolhoda (Measurement)

Managing team coordination incentives: the effect of payoff differentials - Tavana, Madjid; Di Caprio, Debora; Santos-Arteaga, Francisco J. (Journal of Centrum Cathedra)